Hand-foot-mouth disease in the elderly: A case report - Rizky R. Wijayanti; Amelia Pungky; Cut A.W. Sawitri; Agnes S. Siswati; Flandiana Yogianti; Nabila Arkania (Published by Universitas Gadjah Mada, 2026)
Hand-foot-mouth disease (HFMD), commonly caused by Coxsackievirus A16, is a contagious illness characterized by fever and vesicles on the hands, feet, and oral cavities. While well-documented in children, it is exceptionally rare in older adults. The case of a 65-year-old. illustrates this. woman who presented at Dr. Sardjito General Hospital, Yogyakarta, with red spots on her hands and feet. Examination revealed multiple erythematous plaques on her palms, forearms, and lower legs, alongside target-like plaques with pseudo-vesiculation and a solitary oral ulcer. This case underscores the unusual presentation of HFMD in the elderly, highlighting that the disease, though predominantly pediatric, can occur in the elderly. The atypical clinical findings highlight the urgent need for accurate and timely recognition to ensure appropriate management. This report contributes to the growing evidence on HFMD’s clinical spectrum in adults and signals the necessity for further research and case documentation to improve understanding and early diagnosis in the elderly population.